The Relevance of Clinical Legal Education for Law School on Preparing Legal Human Resources in Indonesia - Suhadi, Suhadi (The Indonesian Journal of International Clinical Legal Education, 2019)
The existence of human resources in the field of law, is increasinglydemanded by the society. In order to produce human resources in thefield of law, higher legal education needs to change the orientation ofeducation. Higher legal education needs not only to equip graduateswith technical abilities to analyze the legislation, but it also needs toequip them with knowledge to understand law and justice as a basichuman need. Clinical Legal Education is a learning model that developsinteractive and reflective learning, develops value-sensitive aspects oflaw purposes, instills the spirit of public service and social justice, andestablishes a basis for the development of responsible legalprofessionals. This means that, through the Clinical Legal Educationwhich gives students the opportunity to be willing to pay attention tothe empirical sides of the law. Using this way, the students' legalisticformalisticunderstanding will be enriched with their understanding ofvalues in the society. In this context, the Clinical Legal Education hasrelevance to the legal education in Indonesia in preparing thegraduates of law schools to become human resources in the field oflaw.